2003
DOI: 10.1002/hyp.1313
|View full text |Cite
|
Sign up to set email alerts
|

A two‐step‐ahead recurrent neural network for stream‐flow forecasting

Abstract: Abstract:In many engineering problems, such as flood warning systems, accurate multistep-ahead prediction is critically important. The main purpose of this study was to derive an algorithm for two-step-ahead forecasting based on a real-time recurrent learning (RTRL) neural network that has been demonstrated as best suited for real-time application in various problems. To evaluate the properties of the developed two-step-ahead RTRL algorithm, we first compared its predictive ability with least-square estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…RMSE can provide a good measure of model performance for high flows (Karunanithi et al, 1994), but significant variations in the assessment of different catchments will occur, since the evaluation metric is dependent on the scale of the dataset that is being analysed. It is perhaps better to report RMSE, rather than Mean Squared Error (MSE; Chang et al, 2004;Chen et al, 2006;Furundzic, 1998;Riad et al, 2004;), because RMSE is measured in the same units as the original data, rather than in squared units, and is thus more representative of the size of a "typical" error. MSE was at one point the most widely used measure of overall accuracy for a forecasting method but it is also the method that has incurred the most criticism (e.g.…”
Section: Statistical Parameters Of Observed and Modelled Time Series mentioning
confidence: 99%
See 1 more Smart Citation
“…RMSE can provide a good measure of model performance for high flows (Karunanithi et al, 1994), but significant variations in the assessment of different catchments will occur, since the evaluation metric is dependent on the scale of the dataset that is being analysed. It is perhaps better to report RMSE, rather than Mean Squared Error (MSE; Chang et al, 2004;Chen et al, 2006;Furundzic, 1998;Riad et al, 2004;), because RMSE is measured in the same units as the original data, rather than in squared units, and is thus more representative of the size of a "typical" error. MSE was at one point the most widely used measure of overall accuracy for a forecasting method but it is also the method that has incurred the most criticism (e.g.…”
Section: Statistical Parameters Of Observed and Modelled Time Series mentioning
confidence: 99%
“…Metric Example Studies 1* AME None found 2* PDIFF None found 3 MAE Chang et al (2004); Chen et al (2006); Dawson et al (2006a); Karunasinghe and Liong (2006); Liong et al (2000); Supharatid (2003) (Gupta et al 1998). ME and RMSE are expressed in terms of daily measures by the National Weather Service but the reported equations can be applied to different temporal periods.…”
mentioning
confidence: 99%
“…Chang et al 2004, Pan and Wang 2005, Muluye and Coulibaly 2007, Carcano et al 2008, Coulibaly 2010. Furthermore, none of these studies has investigated the EKF algorithm to perform training of recurrent neural networks for use in hydrology-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-stepahead prediction is a challenging task which attempts to make predictions several time steps into the future. Chang et al (2004) developed a two-step-ahead recurrent neural network for streamflow forecasting. Later they explored three types of multi-step-ahead (MSA) neural networks, viz.…”
Section: Introductionmentioning
confidence: 99%